A Rare Presentation of a Transethmoidal Encephalocele at Birth - Anand Vishwanath Upasani; Dhiren Nanjibhai Patel; Sudhir Bhisham Chandna (Pediatrics and Neonatology)
Transethmoidal encephalocele is a very rare condition. Herein, we report the case of a neonate with a transethmoidal encephalocele, who presented with an externally visible intranasal mass at birth. Clinical suspicion of intracranial extension was confirmed by radiological imaging. A bifrontal craniotomy was done to divide the narrow communicating duct. The mass was delivered through the nostril and duraplasty was completed. The postoperative recovery was uneventful.